Analisis Terhadap Fenomena Kekerasan Seksual yang Terjadi di Lingkungan Pendidikan (Studi Kasus di Kabupaten Cilacap) - Vandi Prahestu, Tri (Proceedings Series on Social Sciences & Humanities, 2024)
Sexual harassment is the abuse of power and expression of male sexuality. Recently, harassment and even sexual violence have often occurred in educational environments. It is hoped that this research will be able to provide additional knowledge and reference or reading material regarding the legal protection of victims of sexual violence. The aim of this research is to analyze the protection received by victims of sexual violence. The research method used uses a juridical-normative concept. Some forms of general protection provided to crime victims are Provision of Restitution and Compensation, Counselling. Victims of crime who experience medical suffering as a result of a crime can receive medical assistance in the form of medical examinations, Legal Aid. Reasons that influence victims not reporting are doubts about whether it is harassment or not, getting advice from people close to them not to report, not wanting conflict, not knowing the flow of reporting cases, not wanting problems and obstacles to occur in the lecture process, imitating the behavior of people around them, think reporting cases is a futile act.